Kepemimpinan Islam yang Berkeadilan: Pelajaran dari Masa Khulafaur Rasyidin - Nasar, Sartina Wati; Syahid, Abdul; Dakir, Dakir (Ummul Qura Jurnal Institut Pesantren Sunan Drajat (INSUD) Lamongan, 2025)
Islamic leadership that is just is an ideal model exemplified by the Rasyidin Khulafaur, namely Abu Bakar Ash-Siddiq, Umar bin Khattab. This period is often considered the best leadership period in Islamic history, where the values ​​of justice, trust and deliberation were consistently implemented in government. This article aims to explore the principles of just leadership applied by the Rasyidin Khulafaur and how they face various political and social challenges. This research uses qualitative methods with a descriptive-analytical approach to analyze the policies and actions of the four caliphs, especially in terms of law enforcement, distribution of wealth, and resolution of internal and external conflicts. The research results show that justice is at the core of every political and social decision taken by the Rasyidin Khulafaur, both in terms of public policy, government transparency, and leader accountability towards the people.